The effects of sea-bottom plowing on phytoplankton assemblages: a case study of northern Hiroshima Bay, the Seto Inland Sea of Japan - Ohara, Shizuka; Yano, Ryoko; Furuya, Kenichiro; Sato, Takafumi; Ikeda, Syunichiro; Koike, Kazuhiko (Frontiers in Marine Science, 2023)
Sea-bottom plowing is originally a method used to oxidize sediment by stirring the bottom with a trawl fishing tool, and its effect in increasing primary productivity of the water column was investigated in the western part of the Seto Inland Sea of Japan. Preliminary field sampling showed that diatom resting stage cells were abundant in the sediment of the tested area at 1.5–2.6 × 105 MPN g-1 wet sediment. When the sediment was added to filtered seawater, diatom cells emerged from the sediment after one day and increased more drastically under a light level corresponding to sunny weather than cloudy weather. In the actual trials of sea-bottom plowing on the field for a continuous period of 4 years, dissolved inorganic nutrients increased at the bottom layer after the plowing and promoted photosynthetic activities of the phytoplankton communities in 2018 and 2021. Chlorophyll a concentration at the middle layers increased 1.06–2.15 times after plowing throughout the trials for 4 years. Diatoms contributed to 67–99% of this chlorophyll a concentrations and included the genera Skeletonema and Chaetoceros, which formed resting-stage cells in the sediment. Pseudo-nitzschia spp. often increased after the plowing, which was assumed to be of seawater origin. Estimated primary productivities of the middle layers dropped once the following day due to turbid water caused by the plowing but increased 2.03–4.41 times after two or five days in 2018, 2019, and 2021. These results suggest that sea-bottom plowing has an enrichment effect on diatoms and could be a possible measure to fertilize the sea.